PERFORMANCE ANALYSIS OF THE SAMA'UN BAKRIE ROAD SECTIONON WEEKENDS AND WEEKDAYS (SERANG CITY – BANTEN) - Wiwien Suzanti; Midia Rahma; Aditya Rahadian Fachrur; Rana Avryan Anatra (ADISAM Publisher, 2025)
Sama'un Bakrie Street is an important road section for the people of Serang City. This is because the road section is widely traversed by residents of Serang City to go to the main market of Rau Trade Center (RTC), besides that the road section is a infrastructure to Serang station and office locations, including the Serang District Public Works Office and Serang Regency DLH. With its proximity to the main market, stations, and office areas, there are many community activities on the road such as pedestrians, stopped vehicles, parking, slow vehicles, and vehicles in and out of the side of the road. This research was conducted for 7 (Seven) days and used the Indonesian Road Capacity Manual method (MKJI, 1997) with the aim of research to analyze the performance of road sections, identify side obstacle problems, road capacity, degree of saturation, and determine the level of service on the Sama'un Bakrie road section Serang City, Banten. The results of the research analysis showed that the highest peak volume in the RTC direction was on Thursday (879 smp / hour) and the highest peak volume in the direction of Serang Station was on Tuesday (769 smp / hour). The road capacity is rated (2535.18 smp/hour) with a very low side obstacle class (Very Low) with an event weight value of <100, and the highest saturation degree value has a value (0.503). This shows that the service level of the performance of the Sama'un Bakrie road section in Serang City, Banten is in category C (0.45-0.74), so that the Sama'un Bakrie road section is in a stable current zone but drivers are limited in choosing speed.